Human Factors and Personnel Purges in the Zafra–Huelva Railway (1936–1975) (TST. Transportes, Servicios y Telecomunicaciones, 2025)
This article presents an analysis of the impact and consequences of the Spanish Civil War on the human resources of the Zafra–Huelva Railway Company. The study, which extends chronologically to the end of the Francoist dictatorship, has been carried out using documentation relating to this subject and to the procedure for the purging of railway personnel, initiated by the rebel army in the early months of the conflict and institutionalized with the enactment of the Law on the Purge of Civil Servants of 10 February 1939, preserved at the Documentary Centre of Historical Memory in Salamanca.
Keywords: Spanish Civil War, Railway, Railway Workers, Personnel Purging.